Getting a Job in Flushing: A Qualitative Study on Chinese Immigrants’ Job-Finding and Job Transitions in an Ethnic Enclave - Liu, Bolei (Qualitative Sociology Review, 2017)
In this study, I investigated how different forms of human capital and social capital of new Chinese immigrants affect their job-search and job transitions in the Flushing area. I conducted sixteen indepth interviews with new Chinese immigrants who were seeking job opportunities within Flushing, documenting not only their personal background but also their immigration and working experiences in both China and the United States. Results indicate that the aggregation of certain human capital has positive influence on immigrants’ income, rather on immigrants’ job-findings and job transitions. The efficiency of social ties, instead of strength of social ties, is a more significant unit of analysis in the co-ethnic labor market. Though immigrants’ efficient social ties may be helpful for finding their first jobs in the U.S., the efficiency of social ties with regards to job-searching may dramatically decrease as immigrants stay longer in the U.S. As a result, social ties may not have a salient influence on immigrants’ job transitions.